Cretaceous granitic intrusions in Fujian Province, Cathaysia Block: Implications for slab rollback and break-off of the Paleo-Pacific plate. (1st April 2020) - Wang, Zhengyi; Zhao, Xilin; Yu, Shengyao; Li, Sanzhong; Peng, Yinbiao; Liu, Yongjiang
Graphical abstract: Highlights: Cretaceous granitic intrusions formed by three magmatic events in SE China. The intensity of crust–mantle interactions increased gradually from 145 Ma to 86 Ma. These granitic intrusions are related to Paleo-Pacific subduction or rollback. Abstract: The geodynamic transformation of the Cathaysia Block and its relationship with the Cretaceous granitic intrusions have been controversial in recent decades. In this study, petrology, zircon U–Pb ages, Lu–Hf isotopic composition, whole-rock geochemistry and Sr–Nd isotopes were carried on Cretaceous granites that were collected from the Fujian province, SE China. Combining previously published ages with the new ages obtained in this study indicates that the magmatism in the study area occurred in three distinct stages at 145–137 Ma, 136–118 Ma and 107–86 Ma. The first stage I-type granites were intruded at 137 ± 1 Ma and 145 ± 1 Ma, which are characterized by low εNd (t) values of −7.3 to −6.8 and εHf (t) values of −12.5 to −2.5. It was formed by partial melting of Mesoproterozoic medium-to-high K basaltic rocks in the thickened crust of ~40 km without significant hybridization of mantle-derived magmas and fractional crystallization. The second stage highly differentiated I-type granites yield zircon U-Pb ages of 125 ± 1 Ma and 128 ± 1 Ma, which contain slightly negative εNd (t) values of −5.4 to −5.3 and εHf (t) values of −8.4 to −3.2. It was generated by partial melting of the Mesoproterozoic basement at the depth of 30–40 km triggered by underplating of a small amount of mantle-derived magma, with primary crustal melts undergoing plagioclase-dominated fractionation crystallization. The third stage I-type granites yield zircon U-Pb ages of 104 ± 1 Ma and 105 ± 1 Ma, which contain εNd (t) values of −1.7 to −7.3 and εHf (t) values of −6.0 to −0.5. It was derived from partial melting of Mesoproterozoic basaltic source at a depth of ~30 km. Besides, a mass of mantle-derived magma was mixed into the crustal melts, accompanied with plagioclase-dominated fractionation crystallization. Combining previously published data and those obtained in this study provides significant information for the tectonic evolution of Paleo-Pacific. In stage 1 (145–137 Ma), the existence of I-type granites and adakitic rocks suggests that the dip-angle subduction of the Paleo-Pacific Plate led to the partial melting of the thickened lower crust under the compressional environment. In stage 2 (136–118 Ma), the generation of I-type and A-type granitic magmas imply the thinning of the lithospheric crust under the extensional environment and the upwelling of the asthenospheric mantle, which are caused by slab rollback of Paleo-Pacific. In stage 3 (107–86 Ma), the appearance of much more I-type and A-type granites indicates that the break-off of the Paleo-Pacific plate led to much stronger crust–mantle interactions under the extensional environment.